Comprehensive evaluation of ubiquitous promoters suitable for the generation of transgenic cynomolgus monkeys†. Issue 6 (14th March 2019) - Seita, Yasunari; Tsukiyama, Tomoyuki; Azami, Takuya; Kobayashi, Kenichi; Iwatani, Chizuru; Tsuchiya, Hideaki; Nakaya, Masataka; Tanabe, Hideyuki; Hitoshi, Seiji; Miyoshi, Hiroyuki; Nakamura, Shinichiro; Kawauchi, Akihiro; et al.
Abstract: Nonhuman primates (NHPs) are considered to be the most valuable models for human transgenic (Tg) research into disease because human pathology is more closely recapitulated in NHPs than rodents. Previous studies have reported the generation of Tg NHPs that ubiquitously overexpress a transgene using various promoters, but it is not yet clear which promoter is most suitable for the generation of NHPs overexpressing a transgene ubiquitously and persistently in various tissues. To clarify this issue, we evaluated four putative ubiquitous promoters, cytomegalovirus (CMV) immediate-early enhancer and chicken beta-actin (CAG), elongation factor 1α (EF1α), ubiquitin C (UbC), and CMV, using an in vitro differentiation system of cynomolgus monkey embryonic stem cells (ESCs). While the EF1α promoter drove Tg expression more strongly than the other promoters in undifferentiated pluripotent ESCs, the CAG promoter was more effective in differentiated cells such as embryoid bodies and ESC-derived neurons. When the CAG and EF1α promoters were used to generate green fluorescent protein (GFP)-expressing Tg monkeys, the CAG promoter drove GFP expression in skin and hematopoietic tissues more strongly than in ΕF1α-GFP Tg monkeys. Notably, the EF1α promoter underwent more silencing in both ESCs and Tg monkeys. Thus, the CAG promoter appears to be the most suitable for ubiquitous and stable expression of transgenes in the differentiated tissues of Tg cynomolgus monkeys and appropriate for the establishment of human disease models. Abstract : Comparative examination of ubiquitous promoters in an in vitro ES cell differentiation system and Tg animals provides fundamental insights into suitable promoters for high-level transgene expression in cynomolgus monkeys.